Optimization of Patrol Implementation by Samapta Units of Sragen Police to Prevent 3C Crimes (Theft by Weight, Violent Theft, and Motor Vehicle Theft) - Rastra, Iqbal (Advances in Police Science Research Journal, 2024)
This study aims to improve the management of organizational resources and the implementation of patrols by the Patrol Unit Samapta Unit of the Sragen Police to prevent 3C crimes (theft by weight, violent theft, and motor vehicle theft) in the context of maintaining public safety and order.   By using the theory of organizational  resources  and POAC management as an knife analysis. Primary data and  secondary data were obtained from interviews of data and documentation (photographs). Data analysis is carried out qualitatively, namely data reduction, data presentation, and drawing conclusions. The research locations are the Sragen Police Station and the Ranks Police Station. The results showed that through the theory of 4M Organizational Resources, the Organizational Resources of the Samapta Unit Patrol Unit of the Sragen Police Can be optimized. As in humans, we can optimize it by conducting periodic training followed by patrol members so that in implementing patrols the ability of members to deal with crimes as expected. Then for the number of personnel that are less likely by way of requesting other units of the Samapta Unit such as members of the dalmas to assist the Patrol. Then for the budget, it may be more concerned about the fuel budget because the number of patrols is quite dense and there are also often increased vulnerable activities. For facilities and infrastructure, it has met the requirements and vehicle maintenance to be more considered because to carry out patrols it is necessary to have vehicles that are suitable for use for the convenience of members carrying out patrols. For the method of implementing  patrols, it prioritizes  dialogical patrols to the community so that we know the problems and what the community wants and to make it easier for members, it is necessary to have patrols intersecting between police departments. Finally, the form of GPS surveillance is good but not optimal because members can only carry out documentation sober. Therefore, through organizational resources and management theory, it can be optimized how the implementation patrol by the patrol unit of the Samapta Unit Sragen Police for the Prevention of 3C Crime (theft by weight, violent theft, and motor vehicle theft) in the context of maintaining public safety and order.